Answer:
-3x+6
Step-by-step explanation:
-3x-6(-1)
First, multiplying two negatives equals a positive: (-)×(-)=(+). Then,
multiply the numbers -3×+6×1 = -3x+6. Then, you got the answer and the answer is -3x+6
Answer:
1. -16-(-11)=5
2.48 divided by -8 is 12
3.13/5=2
4.81-11=7
5.3*2=35
6 35*2=5
Step-by-step explanation:
Answer:
(2/4)/(4/4) = 0.5 or 2/4
Step-by-step explanation:
Compute the slope of the line through (-2, -9) and (-4, -17):
Any line perpendicular to this line will have slope -1/4. The one that passes through (0, 10) satisifes